CONTEMPORARY GENERATIONS OF OFFENSIVE AND DEFENSIVE WEAPONS - SZPAKOWSKA Zuzanna (2018)
The article deals with the problem of distinguishing between offensive and defensive weapons in the context of international security, and its influence on the evolution of wars with particular emphasis on modern times. The nuclear weapon deserves particular attention because of its dual nature – both offensive and defensive, which resulted, among other things, in the development of a strategy of deterrence. What is more, its presence in the arsenals of the great powers causes that international politics is much more prudent, and the classic, territorial concept of security has lost its importance. By analyzing the most important sources of military threats, the author concretizes her reflections on the example of Poland, and its contemporary situation regarding the issues discussed. The main research problem raised in this article is the question – what is the impact of modern weapons generations on international politics in the context of military security?